2010
DOI: 10.1038/cddis.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of amyloidogenic immunoglobulin light chains in cell culture

Abstract: Light-chain amyloidosis (AL) is a devastating protein-misfolding disease characterized by abnormal proliferation of plasma cells in the bone marrow that secrete monoclonal immunoglobulin light chains that misfold and form amyloid fibrils, thus causing organ failure and death. Numerous reports on different protein-misfolding diseases show that soluble oligomeric species populated by amyloidogenic proteins can be quite toxic to cells. However, it is not well established whether the soluble immunoglobulin light-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…Later on, experiments conducted with soluble fractions from preparations of amyloid affected tissue showed that soluble species were as toxic as or more toxic than insoluble amyloid fibrils. Recent work done by our laboratory and others has shown that the presence of soluble AL proteins in cell culture induces apoptosis (Shi et al, 2010;Sikkink & Ramirez-Alvarado, 2010). In particular, we were able to demonstrate that the light chain species present in cell culture at the time of maximum apoptotic activity are primarily light chain monomer and dimers.…”
Section: Cellular Toxicity Studiessupporting
confidence: 53%
“…Later on, experiments conducted with soluble fractions from preparations of amyloid affected tissue showed that soluble species were as toxic as or more toxic than insoluble amyloid fibrils. Recent work done by our laboratory and others has shown that the presence of soluble AL proteins in cell culture induces apoptosis (Shi et al, 2010;Sikkink & Ramirez-Alvarado, 2010). In particular, we were able to demonstrate that the light chain species present in cell culture at the time of maximum apoptotic activity are primarily light chain monomer and dimers.…”
Section: Cellular Toxicity Studiessupporting
confidence: 53%
“…Organ dysfunction in AL amyloidosis is not only a result of organ architecture disruption, but there is a direct cytotoxic effect of the amyloidogenic LCs [17,18]. This observation explains the rapid clinical improvement of successfully treated patients evidenced by biochemical organ recovery, before a reduction in the amyloid deposits at the affected organ(s) can occur.…”
Section: Pathogenesismentioning
confidence: 88%
“…The amyloidogenic protein AL-09 internalizes faster than the germline I, which could be correlated with its lower thermodynamic stability and its higher amyloidogenic propensity (13,36). Soluble proteins do not accumulate on the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble monoclonal LC, isolated from patients with amyloidosis, can impair rat cardiomyocyte function (11) and induce apoptotic events in mouse cardiomyocytes (12,13). Also, urinederived LC can be internalized into primary rat cardiac fibroblasts (14) and primary human renal mesangial cells (15) through a pinocytic pathway (16) or via receptor, clathrin-mediated mechanisms, respectively (15).…”
Section: Light Chain (Al)mentioning
confidence: 99%
See 1 more Smart Citation